Effects of nano-sizing on lipid bioaccessibility and ex vivo bioavailability from EPA-DHA rich oil in water nanoemulsion. (1st March 2019) - Dey, Tanmoy Kumar; Koley, Hemanta; Ghosh, Mahua; Dey, Sanjit; Dhar, Pubali
Highlights: Nanoemulsion (≤200 nm) has enhanced lipid absorption across rat enteric epithelium. Enhanced bioavailability of PUFAs in all three small intestinal segments. Nanoemulsion (NE) was more rapidly absorbed than conventional emulsion in PBMCs. NE shows better antiinflammatory response due to better bioavailability in PBMCs. Abstract: The physiological efficacy of nutraceuticals is dependent on their physicochemical nature and bioavailability across biological barriers. In the present work, effects of nano-sizing of emulsion-based delivery vehicle on the bioavailability of polyunsaturated fatty acids rich fish oil have been investigated via three-step experimental design; ex vivo rat everted intestinal sac model, cellular lipid uptake and the bioactivity in rat PBMCs. Nanoemulsion in comparison to the conventional emulsion has shown significant higher rate of uptake of polyunsaturated fatty acids in three segments of small intestine. The time-kinetics of such uptake was correlated with appearance of short-chain fatty acids in basal side of the everted sac. The bioavailability of the formulated fish oil and its inhibitory response against lipopolysaccharide-induced nitric oxide production in rat PBMCs were positively correlated. This formulation with nano-sized droplets can be utilized as smart delivery vehicles for designing oral therapies in future.